Effects of energy drink major bioactive compounds on the performance of young adults in fitness and cognitive tests: a randomized controlled trial (2014)
ABSTRACT: Background: The consumption of beverages containing caffeine and taurine before exercising has been associated with increased physical and psychological performances and has been promoted to support the emotional state and provide vitality to consumers. However, there are contradictory results on these issues, it is not clear the effect of every major compound in relation to the whole effect of the beverages and there is a lack in knowledge about their degree of safety for consumption. Methods: This study used a double-blind, placebo controlled, randomized, crossover design. Fourteen male volunteer soldiers from the Colombian army performed different tests to measure their cardiorespiratory fitness (VO2max and maximum heart rate), time to exhaustion, strength (isometric strength), power (vertical jump), concentration (Grid test) and memory (Digits test) after drinking 250íml of one of the following beverages: one with 80ímg caffeine, one with 1000ímg taurine, one with 80ímg caffeine plus 1000ímg taurine, a commercial energy drink (Red Bullí) or a placebo drink. Subjects were caffeine-consumers that avoided caffeine during the day of evaluation. All beverages were matched in flavor and other organoleptic properties to the commercial one, were bottled in dark plastic bottles and were administered in identical conditions to the participants. Differences between treatments were assessed using repeated measures and analysis of variance. Results: The mean í SD values of VO2max, maximum heart rate, time to exhaustion, right handgrip strength, left handgrip strength, vertical jump, Grid test and Digits test were 61.3 í 6.2íml/kg.min, 196 í 6.8 beats per min, 17 í 1.2ímin, 56.8 í 6.6íkgf, 53.1 í 5.9íkgf, 41.1 í 3.8ícm, 19.9 í 5.9 observed digits and 10.9 í 3.1 remembered digits after drinking a placebo drink. Comparisons among the commercial drink, caffeine, taurine, caffeine plus taurine and placebo treatments did not show statistically differences in the results of the performed tests. No adverse effects were reported by the participants. Conclusion: The consumption of caffeine (80ímg) and taurine (1000ímg) or their combination does not increase the physical and cognitive ability in young adults during exercise.